PENGARUH EDUKASI GIZI ANAK USIA 3-5 TAHUN TERHADAP PENGETAHUAN IBU DI RUMAH SAKIT HORAS INSANI PEMATANGSIANTAR - Tampubolon, Rosalyn; Lenny Lusia Simatupang (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Nutrition is an aspect related to the basic function of nutrients that produce energy, growth and tissue maintenance and regulate metabolic processes in the body. By having nutritional knowledge, mothers can create good food consumption patterns for children. The type of research used is quantitative research. The design of this study uses the Quasi-experimental method with a one group pretest posttest design. This study uses a purposive sampling technique, namely a method of drawing samples by selecting subjects based on certain characteristics. This study used 38 respondents as an experimental group. The results of this study before education was given to mothers, namely the majority of knowledge was lacking as many as 26 respondents (68.4%) and a minority of good knowledge as many as 2 respondents (5.3%), the results of the study after education was given to mothers, namely the majority of knowledge was good as many as 23 respondents (60.5%) and a minority of knowledge was lacking as many as 2 respondents (5.3%). The analysis in this study used the Paired t-test statistical test with a confidence level of 95% (α = 0.05), so the results obtained were p-value 0.001 <α (0.05). The influence of this education has a good effect on maternal knowledge, making mothers think more critically in determining nutrition for children.